Genetic variants of the HLA-G/LILRB1 ligand-receptor axis in donors or recipients are prognostic covariates for rejection after living kidney transplantation - Hölzenbein, Julian; Schramm, Sabine; Heinemann, Falko M.; Heinold, Andreas; Gäckler, Anja; Reinold, Johanna; Wilde, Benjamin; Busch, Yannik; Gruenen, Nina; Peter, Wolfgang; Horn, Peter Alexander; Witzke, Oliver; et al. (Frontiers in Immunology, 2026)
BackgroundHLA-G is a non-classical HLA class I molecule that promotes transplant tolerance. It engages the inhibitory receptor LILRB1 on immune effector cells, suppressing cytotoxic responses and inflammation, while promoting tolerogenic and regulatory immune phenotypes. Polymorphisms in the HLA-G 3′ untranslated region (3′UTR) modulate HLA-G expression levels, and LILRB1 promoter variants influence receptor expression. The combined effect on kidney transplant (KTx) rejection has not been systematically studied.MethodsLiving donor–recipient pairs undergoing KTx were genotyped for nine variants in the HLA-G 3′UTR region and two single nucleotide polymorphisms (SNPs) in the LILRB1 promoter (PROMO) regions. Haplotypes were arranged for both loci. Clinical endpoints were biopsy-proven T cell-mediated rejection (TCMR) within one year and antibody-mediated rejection (AMR) within five years post-transplant.ResultsDonor positivity for HLA-G 3′UTR-1 or UTR-2 or negative for UTR-3 haplotype were associated with a significantly higher risk of TCMR in both univariate or multivariate analyses. Recipients lacking the LILRB1-PROMO CG haplotype also had an increased TCMR risk. The combination of an HLA-G 3’UTR-2 positive donor with a LILRB1-PROMO CG haplotype negative recipient was found to be an independent predictor of TCMR. In contrast, HLA-G 3′UTR variants were not associated with AMR, while the presence of the recipient LILRB1-PROMO CG haplotype emerged as an independent AMR risk factor.ConclusionsDonor HLA-G 3’UTR and recipient LILRB1-PROMO haplotypes define a functional immunogenetic axis that differentially influence TCMR and AMR. These results support the clinical potential of HLA-G/LILRB1 genetic profiling to improve donor selection in living KTx and to guide the development of novel rejection therapies.